Differential expression of T cell antigens in normal peripheral blood lymphocytes: a quantitative analysis by flow cytometry. - Ginaldi, L (1996)
AIMS: To obtain reference values of the level of expression of T cell antigens on normal lymphocyte subsets in order to disclose differences which could reflect their function or maturation stages, or both. METHODS: Peripheral blood from 15 healthy donors was processed by flow cytometry with triple colour analysis. For each sample phycoerythrin (PE) conjugated CD2, CD4, CD5, CD8, and CD56 monoclonal antibodies were combined with Cy5-R-phycoerythrin (TC) conjugated CD3 and fluorescein isothiocyanate (FITC) conjugated CD7; CD2- and CD7-PE were also combined with CD3-TC and CD4-FITC. Standard microbeads with different capacities to bind mouse immunoglobulins were used to convert the mean fluorescence intensity (MFI) values of the lymphocyte subsets identified by multiparametric flow cytometry into the number of antigen molecules per cell, measured as antibody binding capacity (ABC). RESULTS: CD4+ (helper/inducer) T cells exhibit a higher CD3 antigen expression compared with CD8+ (suppressor/ cytotoxic) T lymphocytes. Within the CD4+ T cells, the CD4+CD7- subset expressed a lower level of CD3 compared with CD4+CD7+ and CD8+CD7+ cells, and higher CD2 and CD5 expression than the main CD3+CD7+ subset. Major differences in antigen expression were also detected between CD3+ T cells and CD3-CD56+ natural killer (NK) cells: NK cells exhibited higher levels of CD7 and CD56 and lower levels of CD2 and CD5 than T cells. Significantly lower CD5 expression was also detected in the small CD5+ B lymphocyte subset compared with T cells. CONCLUSIONS: Quantitative flow cytometry with triple colour analysis may be used to detect antigen modulations in disease states and to increase the accuracy of diagnosis by comparison with findings in normal counterparts.